Comparative biological resistance of differently thermal modified wood species against decay fungi, Reticulitermes grassei and Hylotrupes bajulus - Hüseyin Sivrikaya; Ahmet Can; Teresa de Troya; Maria Conde (Maderas: Ciencia y Tecnología, 2021)
Thermal modified wood has some advantages over natural wood, including decreased hygroscopicity, increased dimensional stability, and enhanced durability. In this study, European species of Scots pine (Pinus sylvestris), spruce (Picea orientalis), ash (Fraxinus spp.), and tropical species of tali (Erythrophleum ivorense), and iroko (Chlorophora excelsa) were thermally treated at 180 °C and 210 °C for 1,5 and 2 h, respectively. We evaluated the resistances of the untreated and thermally treated samples to decay induced by the white rot fungus, Trametes versicolor and two brown rot fungi, Coniophora puteana and Postia placenta. In addition, the samples were exposed to the termite Reticulitermes grassei and the longhorn beetle species Hylotrupes bajulus to evaluate their resistance to damage by the insects. During the heat treatment, the mass loss of the samples generally was between 9 and 14%. After the heat treatment, experiments were conducted to determine the effects of white and brown rot fungi on samples of Scots pine and tali, the effect of C. puteana on spruce, and the effects of C. puteana and P. placenta on ash and iroko. In all experiments, the mass loss due to damage from the various fungi was less than 1% for the samples that had been heat treated at 210 °C. The untreated and heat-treated tropical species exhibited higher durability with very low mass loss and 100% mortality of the insects when attacked by termites, whereas the other wood species had moderate attack. In addition, Hylotrupes bajulus exposure by two standart methods (EN 46 and 47) resulted in similar performances in most cases, although EN 47 treated samples at 210 °C showed improved durability for Scots pine (Pinus sylvestris) and spruce (Picea orientalis).